USAGE OF ISLAMIC TERMS IN COMPARATIVE LINGUISTICS - Feruza Khodjakulova Rustamovna (Лучшие интеллектуальные исследования, 2024)
Abstract: This article presents a comprehensive analysis of the usage of Islamic terms in the field of comparative linguistics. Comparative linguistics is a branch of linguistics that aims to establish relationships between languages, reconstruct their historical development, and understand their structural similarities and differences. The precise usage of terms in this field is of utmost importance to ensure clear communication and accurate interpretation of linguistic data. The article begins by examining the fundamental concepts and principles of comparative linguistics, emphasizing the importance of terminology in facilitating accurate comparisons and systematic analyses. It explores various linguistic terms, such as cognates, loanwords, phonological shifts, and morphological changes, which are essential for conducting comparative studies.